Location of Two Fire Stations in Five Sub-Metros of the Kumasi Metropolis - Amo-Asante, Kwadwo (2013)
A Thesis Submitted To the Department of Mathematics, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirement for the degree of Master of Science in Industrial Mathematics